Making virtual project-based learning work during the COVID-19 pandemic - KUSNADI, Yuanto (Institutional Knowledge at Singapore Management University, 2022)
Project-based learning is an increasingly popular pedagogical approach in university education shown to be effective in fostering problem-solving, analytical, design thinking and teamwork skills. The COVID-19 pandemic has led to universities pivoting from project-based learning (PBL) in the classroom to a virtual learning environment. By examining local student consulting courses conducted virtually in a Singapore University (UNIS) during the COVID-19 pandemic, this study aims to address the knowledge gap in the PBL literature by identifying the roles played by digital literacy - in utilising the digital tools that support virtual learning, in a virtual learning environment. The study also serves to highlight students’ major takeaways in virtual PBL setting.